2018
DOI: 10.1097/mrr.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the usability of a standard and an age-friendly smartphone launcher: experimental evidence from usability testing with older adults

Abstract: Age-friendly smartphone launchers are tools designed to enhance smartphone handling among older adults with cognitive and functional limitations. Although evidence exists about the positive effects of age-friendly smartphone launchers on older adults' usability performance in general, little is known about how the design and interface complexity of these launchers affect their interface usability effectiveness and efficiency compared with standard Android smartphone interfaces. Thus, in this study, a randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Smartphone medication management apps hold promise with respect to helping individuals with this task [19]. Likewise, smartphone rehabilitation apps were shown to be promising for delivering therapeutic treatment to (older) patients, improving not only their health conditions but also other aspects of quality of life [20]. While technology proficiency benefits all, the benefits to older adults may be especially great [9], [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smartphone medication management apps hold promise with respect to helping individuals with this task [19]. Likewise, smartphone rehabilitation apps were shown to be promising for delivering therapeutic treatment to (older) patients, improving not only their health conditions but also other aspects of quality of life [20]. While technology proficiency benefits all, the benefits to older adults may be especially great [9], [21].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of the presented study was to address these limitations, using a dataset that included both the MDPQ-46 information and objective measures of smartphone performance [20], with a special focus on advancing the understanding of the construct [24] and criterion validity [25]. The aim of this paper is to establish the construct validity of MDPQ-46 with convergent and discriminant validation, as well as to assess criterion validity by comparing selfreported proficiency with an objective measure of proficiency (i.e., task performance metrics collected in usability tests).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the calendar devices are less capable of being used in some older people [23]. Petrovčič et al [24], in their research, found that more than half of their respondents were able to use calendar devices as reminders to help them remember the day and date, record specific events, and remind them to the following schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Barrier BA1' small font, screen size, font type, buttons, and color contrast' has the highest priority. Barrier BA15 "complex interface and function" is the 2nd critical barrier [30,33,39]. BA6 "Visual feedback of operation" is the third higly cited usablity barrier in the reported literature [32].…”
Section: Proposed Methodologymentioning
confidence: 99%